PENEGAKAN HUKUM TERHADAP PELAKU USAHA KEGIATAN-KEGIATAN YANG DILARANG - Eka Susylawati (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2008)
The Law Number 5 of 19991 abaut Monopoly practice and unfair bussines competition is one legal refor claims. It is hoped to be able to regulate a good bussines to build a fair competition. Beside “forbidden commitments” form, the law also regulate “forbidden activities”. The kinds of  forbidden activities are monopoly, monopsony, marketing segment control and conspiracy. In practice, the law enforcement cannot go smoothly because of multi interpretation definition of forbidden activities and bussiness competition control commission (KPPU). KPPU can only give administrative sanction. While the penal, civil law and appeal effort should be through the court. The other problem is related to the small number of KPPU members when compared to the number of bussinesses that must be controlled and spead through out Indonesia.